2021
DOI: 10.1007/jhep05(2021)099
|View full text |Cite
|
Sign up to set email alerts
|

The electro-weak phase transition at colliders: confronting theoretical uncertainties and complementary channels

Abstract: We explore and contrast the capabilities of future colliders to probe the nature of the electro-weak phase transition. We focus on the real singlet scalar field extension of the Standard Model, representing the most minimal, yet most elusive, framework that can enable a strong first-order electro-weak phase transition. By taking into account the theoretical uncertainties and employing the powerful complementarity between gauge and Higgs boson pair channels in the searches for new scalar particles, we find that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 137 publications
(163 reference statements)
1
55
0
Order By: Relevance
“…At two benchmark points in the xSM, we have demonstrated the numerical importance of these theoretical considerations for the determination of properties of the phase transition. We have found that calculations at less than O(g 4 ) accuracy show a very large renormalisation scale dependence, in agreement with previous studies in other models [56,58,94,130]. We also remarked that while we were able to perform a complete O(g 4 ) calculation for T c and α c , this is currently out of reach for the bubble nucleation rate and bubble wall speed, imparting a limiting source of uncertainty for the gravitational wave spectrum.…”
Section: (B) Bm2supporting
confidence: 89%
See 1 more Smart Citation
“…At two benchmark points in the xSM, we have demonstrated the numerical importance of these theoretical considerations for the determination of properties of the phase transition. We have found that calculations at less than O(g 4 ) accuracy show a very large renormalisation scale dependence, in agreement with previous studies in other models [56,58,94,130]. We also remarked that while we were able to perform a complete O(g 4 ) calculation for T c and α c , this is currently out of reach for the bubble nucleation rate and bubble wall speed, imparting a limiting source of uncertainty for the gravitational wave spectrum.…”
Section: (B) Bm2supporting
confidence: 89%
“…However, as recently emphasised in ref. [56,57], such one-loop computations suffer from huge theoretical uncertainties due to thermal enhancements of infrared physics, significantly limiting the possibility of making quantitative conclusions. These amount to orders of magnitude uncertainty in the peak amplitude of the gravitational wave spectrum.…”
Section: Jhep06(2021)069mentioning
confidence: 99%
“…According to the SU (2) L quantum number of a given representation, the extended scalar could be classified as real or complex singlet, doublet, real or complex triplet, quadruplet, and so on. These new scalars usually affect the electroweak symmetry breaking pattern and in principle may catalyze a first order electroweak phase transition (EWPT) [13][14][15][16][17][18][19]. Furthermore, in some cases these scalars could provide the dark matter candidates [20][21][22][23][24][25][26][27][28][29][30][31] or mechanism for neutrino mass generation [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…In the standard perturbative approach, the effective potential receives contributions from the tree-level potential, the one-loop Coleman-Weinberg correction and its finite-temperature counterpart, as well as Daisy resummations, which together leads to a gauge dependent result (see, e.g., refs. [119,120] for a study of the uncertainties with this approach). A gauge independent result nevertheless can still be obtained if only the leading order thermal correction at the high temperature is kept [121].…”
Section: Electroweak Phase Transitionmentioning
confidence: 99%